CONVENTIONAL INDIRECTNESS STRATEGIES ON REQUEST USED BY MALE AND FEMALE SPEAKERS IN SPOKEN BRITISH NATIONAL CORPUS - Tantri Refa Indriarti; Yulia R. Mawarni (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This study aims at analysing conventional indirectness strategies on request used by British English speakers as shown in spoken British National Corpus (BNC). Conventional indirect strategy is often rated as the most polite expression of politeness. In this case, male and female obviously have different strategies for making the request, which may be influenced by some factors. A qualitative approach was employed to conduct this study since the data are the utterances produced by male and female speakers in spoken BNC. The study revealed that there were 187 utterances that contain Conventional Indirectness Strategies on request used by male and female speakers in spoken BNC. Ability conditions was the strategy of conventional indirect request that mostly used by the male and female speakers. Then, the three factors (i.e. gender, age, and social class) have an effect and significant role on the speaker’s choice of strategies employed by British English speakers. As this study is focused on the indirect request strategies, thus it is suggested to the next researchers who are interested in the same study could be expected to conduct the indirect request strategies by adding more factors.